Out with the old: Hsp90 finds amino acid residue more useful than co-chaperone protein - Abbey D. Zuehlke; Leonard Neckers (Microbial Cell)
Redundant functions maintained from single to multi-cellular organisms have made Saccharomyces cere-visiae an important model for the analysis of con-served com-plex cellular processes. Yeast has been especially useful in understanding the regulation and function of the essential molecular chaperone, Heat Shock Protein 90 (Hsp90). Research focused on Hsp90 has determined that it is highly regulated by both co-chaperones and posttranslational modifications. A recent study per-formed by (Zuehlke et al., 2017) demonstrates that the function of one co-chaperone in yeast is replaced by posttranslational modification (PTM) of a single amino acid within Hsp90 in higher eukaryotes.